Immunoprofile of childhood diabetes - Meritxell Espino-Guarch (15430868) (2023)
Poster by Meritxell Espino-Guarch (Sidra Medicine), Rana Nahas (Sidra Medicine), Taushif Khan (Sidra Medicine), Susi Huang (Sidra Medicine), Anna Halama (Weill Cornell Medicine-Qatar), Khalid Hussain (Sidra Medicine), and Nicholas van Panhuys (Sidra Medicine) Background: The incidence of T2D has increased significantly in recent years and is characterized by impaired insulin secretion, glucose intolerance and hyperglycemia and is highly associated with a modern sedentary lifestyle and obesity. Despite having distinctly different pathologies, both types of diabetes are associated with defects in immune regulation that mediate sensitivity to insulin. Considering that T cells are an attractive target to modulate for therapeutic purposes and that the immunopathology of T2D in human subjects, has not been widely assessed.  Objective: Based on next-generation tools we investigated the transcriptomics differences between Treg and Tcon cells and correlated these with the inflammatory proteins and metabolites present during the development of insulin resistance and T2D. Methods: Here we collected transcriptomic and metabolomic data from 86 children under 17 years-old to identify the regulatory events that participate in IR development. A comparative analysis of the transcriptome of the two major subtypes of CD4+ T cells, regulatory-T cells (Treg) and conventional T cells (Tcon) was conducted and compared with the plasma metabolome of 14 Control, 19 Obese, 17 Pre-diab, 16 T2D, and 20 T1D cases. Additionally, all samples were immunoprofiled by multi-parameter flow cytometry to assess the comparative levels of circulating adaptive and innate immune cell types present that potentially contribute to disease progression.  Results: No significant differences between the absolute proportions of Treg and Tcon subsets present was observed in any of the groups studied. However, a differential analysis of CD49d expression on CD4+ T cells reveled distinct differences between the clinical phenotypes studied. CD49d (ITGA4) is a membrane protein active in pro-inflammatory T cells and participates in cellular migration to tissue. In all clinical phenotypes (obese, Pre-diab, T2D and T1D) CD4+ Treg cells showed increased expression of CD49d in comparison to controls, whereas in Tcon cells differences only were observed in the T2D group. In order to be functional, the CD49d integrin needs to form a heterodimer with ITGB1 protein. When transcriptomic data was interrogated, an imbalance between ITGA4/ ITGB1 was observed in all groups where CD49d showed increased expression. Associated with these findings, anti-inflammatory Treg cytokines including IL-10 were decreased in T2D patients and elevated plasma levels of IL-17, which contributes to the insulin resistance and inflammation were observed. Conclusion: Data generated phenotyping this cohort is currently being further integrated and investigated in order to better understand the immunopathology of T2D progression in children, with the future goal of modulating T cell functionality for therapeutic use.